Pengembangan media berbasis website pada pembelajaran Al-qur`an hadist - Yudhi Septian Harahap; Mardianto Mardianto; Salminawati Salminawati (Indonesian Counselor Association (IKI), 2024)
Media is the main factor that supports the success of learning. The use of monotonous media and limited lesson time makes learning less effective. This study aims to (1) Analyze the process of developing website-based media in learning Al-Qur'an Hadith class XI, (2) Test the feasibility of website-based media, and (3) Analyze the effectiveness of the media. This research uses the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The focus of this research is class XI MAS Nurul Hadina Patumbak consisting of 30 students. Data were collected using qualitative and quantitative techniques. The results showed that the development of website-based media has successfully increased the effectiveness of learning Al-Qur'an Hadith with excellent validity from material experts, IT experts, and learning practitioners. Field trials showed the level of media effectiveness with an average percentage of 91.01%, which is included in the very good category.